PENGARUH GAYA BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS XI IPS MAN 2 CILACAP - Tri Almunawaroh; Yogi Nurfauzi; Putri Tus Welani (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
The learning outcomes of class XI MAN 2 Cilacap students still do not meet the KKM. Even though the learning methods used by the teacher are quite good for the student-centered learning method, it is possible that there is a discrepancy between the learning method and the student's learning style. This study aims to determine the characteristics of the learning styles of class XI social studies MAN 2 Cilacap students in economics subjects and find out the influence of these learning styles on their learning results. Based on its objectives, this study employs a quantitative approach, including correlational research. The population of this study was 194 students, with a sample size of 65 students. A questionnaire is used as a research instrument in the data collection technique. In addition to questionnaires, researchers also use documentation, observations, and unstructured interviews to explore additional data so that the necessary data can be collected. To find out the relationship between variables, the analysis of the determinant coefficient is used, while the hypothesis test uses the t test. As a result, 47% had a visual learning style, 30.77% had an auditory learning style, and the remaining 21.53% had a kinesthetic learning style. The learning outcomes of students in economics subjects who have reached the KKM score are 63%, and the remaining 37% have not reached the KKM score. Furthermore, based on the results of hypothesis testing, learning styles have a positive and significant effect on student learning outcomes. This means that the more appropriate the application of the student's learning style, the better the study's results. Vice versa, the application of learning styles that are not in accordance with the character of students makes learning outcomes less optimal. This is evidenced by the value in the T test results, which show that the calculated t is 6.060 > the table t value is 1.998, and the significance rate is 0.000 < 0.05. So it can be stated that the H1 hypothesis is accepted and H0 is rejected.